Algorithm to detect and calculate the cerebrospinal fluid (CSF) through Magnetic Resonance Imaging (MRI) - González-Martín, Enrique; Sosa-Gómez, Guillermo; Rojas, Omar (EAI Endorsed Transactions on Pervasive Health and Technology, 2019)
INTRODUCTION: An heuristic algorithm for detection and segmentation of cerebrospinal ﬂuid through magnetic resonance imaging is presented.OBJECTIVE: The objective of the method is to calculate the minimum amount of anesthesia to be used in patients at the time of an operation and thus make a decision based on the algorithm.METHODS: The pattern-based CSF segmentation algorithm presented is based on ﬁnite cellular automata that takes as input light and dark images obtained from MRI methods.RESULTS: Based on Fieldman’s test, results show that the algorithm is as eﬃcient as the decision taken by two diﬀerent operators regarding the mL of anesthesia to be used in the patient.
Keywords: Cerebrospinal Fluid (CSF); Magnetic Resonance Imaging; Image Registration; region growing